Temporal and Spatial Variation in Riparian Vegetation and Floodplain Aquifers on the Regulated Dolores River, Southwest Colorado, USA. (1st June 2016) - Dott, C. E.; Gianniny, G. L.; Clutter, M. J.; Aanes, C.
Abstract: The importance of flow variability and floodplain water table recharge for the establishment and long‐term survival of riparian vegetation has been well‐documented. However, temporal and spatial variation in floodplain aquifers has received less attention, although native species can have narrow tolerances for groundwater decline. Our observations of decreased cottonwood cover on floodplains and increased willow cover on river banks since dam completion on the Dolores River led to comparisons between three long‐term study sites above and below McPhee Dam. We summarize 5 years (2010–2014) of shallow groundwater well data from transects of three wells per site. Vegetation cover data were collected from quadrats and line‐intercept transects. In the willow zone, groundwater well levels mirror in‐channel flows and rarely drop below 0.6 m from ground surface. Willow cover and stem counts on point bars are higher at dammed sites. Wells in the cottonwood zone indicate that alluvial recharge happens only during prolonged peak discharge during spring snowmelt or dam release. Years with no dam spill reduced connectivity between surface flows and groundwater, and groundwater depth dropped to between 2 and >2.5 m. Long‐term data below the dam indicate that canopy cover of the dominant cottonwoods has declined over time (48% in 1995, 19% in 2003), especially in the wake of severe drought. Mature cottonwood cover is significantly higher at the undammed site ( p = 0.025). Our results indicate that floodplain habitats below dams exist under artificially extreme drought and inform how biologically diverse riparian systems will be impacted by a drying climate. Copyright © 2016 John Wiley & Sons, Ltd.